Early Marriage In Aceh 2014 - Rahmi, Nuzulul (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Early marriage is a phenomenon that occurs in Indonesian society lately. It has been a part of the culture of the people themselves. Somehow, it is difficult to remove because it has become the habits of Indonesian people, and moreover, they used to it. The aim of this research is to find out the figure description of early marriage in Aceh province 2014. This study is a descriptive study that used cross sectional approach. The population is all of the young couples of reproductive age who are under 20 years old in Aceh province, they are 800,968 couples. And the sample is the total number of population. The data of this research was taken in February, 2015, according to the data from Badan Koordinasi Keluarga Berencana Nasional (BKKBN) of Aceh province. The result of data stated that there are 23 regencies in Aceh province, and Aceh Timur has the most young couples of reproductive age who are under 20 years old, there are 3,987 couples, the second is Aceh Utara with 3,160 couples, and the third is Aceh Barat with 3,012 couples. On the other hand, Sabang took the first place that has the least young couples of reproductive age who are under 20 years old, there are only 20 couples, the second is Banda Aceh with 106 couples and the third is Langsa with 173 couples. It shows us that a rural area has higher possibility in conducting early marriage than an urban area. Everyone should pay attention to it in order to decrease the numbers of early marriage in Aceh province.